Strengthening Village Medium-Term Development Plans (RPJM Desa) Through Indicator Dissemination: A Case Study in Wonosobo Regency - Rahman, Yozi Aulia; Prajanti, Sucihatiningsih Dian Wisika; Hermanto, Agus; Setiawan, Avi Budi; Fauzi, Ahmad Syahrul (Universitas Negeri Semarang, 2025)
The Village Medium-Term Development Plan (RPJM Desa) is a strategic planning document formulated for a six-year period, outlining the village’s vision, mission, policy directions, and development priorities. The preparation of the RPJM Desa is carried out by the village government in collaboration with representatives from various community sectors. Parikesit Village, located in Kejajar District, Wonosobo Regency, Central Java Province, holds potential as a nature-based tourism village that could improve the community's economic welfare. However, it is also categorized as a landslide-prone area with a relatively high risk of natural disasters. This community service activity was implemented in collaboration with the Parikesit Village Government through the dissemination of indicators and technical guidance on RPJM Desa formulation to both the community and village officials. The program employed a participatory approach involving socialization and facilitation to ensure active engagement of all village stakeholders. The primary objective of this activity was to enhance stakeholders’ understanding of the indicators and procedures for preparing the RPJM Desa in accordance with national guidelines. The results of this program indicate a significant improvement in the understanding of both community members and village officials regarding the preparation of an RPJM Desa document that aligns with the village’s local potential and actual needs. This activity has contributed to strengthening the village’s institutional capacity for participatory and locally grounded medium-term development planning.